Accuracy Assessment of RTK, PPK, and PPP-AR Techniques for Direct Georeferencing in UAV-Based Photogrammetric Mapping - M. Arkalı; M. E. Atik (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
In the fields of mapping, surveying, and three-dimensional (3D) modeling, unmanned aerial vehicle (UAV) systems have become essential equipment in recent times. UAVs are increasingly widely used, especially in the field of photogrammetry. The integration of technologies such as digital cameras, inertial measurement unit (IMU), and Global Navigation Satellite System (GNSS) has improved the quality and accuracy of photogrammetric products. In comparison to conventional methodologies, UAVs present a cost-effective alternative to traditional aerial photogrammetry. Recent advancements in technology substantiate their efficacy across a variety of applications. The utilization of direct georeferencing minimizes the reliance on ground control points (GCP). With the advancements in positioning techniques, the accuracy of the products is concurrently improving. Real-Time Kinematic (RTK) and Post-Processed Kinematic (PPK) techniques play a critical role in enhancing the accuracy of UAV-based photogrammetry. Both techniques are widely used in UAV-based photogrammetry. However, relative positioning poses limitations to the study in terms of infrastructure and cost. PPP (Precise Point Positioning), a specific form of absolute positioning, is utilized effectively across various applications. The PPP method, used globally with a single GNSS receiver, is more cost-effective than relative methods. In this study, the performance of the PPP-AR technique as an alternative to the relative methods RTK and PPK is evaluated. Thus, the applicability of the PPP technique, which has improved accuracy and precision with ambiguity resolution, in UAV-based photogrammetry is examined. RTK and PPK techniques achieve Root Mean Square Error (RMSE) values of less than 10 centimeters. In contrast, RMSE values at the decimeter level are observed in the PPP-AR technique.